Defining advanced practice in radiation therapy: A feasibility assessment of a new healthcare provider role in Ontario, Canada. Issue 3 (August 2019) - Harnett, N.; Bak, K.; Zychla, L.; Gutierrez, E.; Warde, P.
Abstract: Introduction: This study assesses the feasibility of a new role for radiation therapists in Ontario, Canada, called the Advanced Practice Radiation Therapist (APRT), which would address health service pressures and improve patients' access to care. Methods: A literature search and expert consensus were used to define advanced practice. A standardized template was used to record each APRTs activities/competencies, along with the requisite knowledge, skills and judgment required to perform these competencies. A thematic analysis of the lists was undertaken to develop a single competency profile. Seven APRTs were deployed at four cancer centres to gather contextual information on the development and integration of the new role. Results: The definition of AP consists of seven key traits and includes a framework identifying stages of practice from entry-level practitioner through expert to advanced practitioner. The competency profile consists of clinical, technical and professional domains which further define the scope of practice and shepherd the role through stages of implementation. Role testing showed support for the role and demonstrated that APRTs can deliver specialized services, perform delegated tasks and their work can lead to program efficiencies and new services. The new role may also lead to improved radiation therapist recruitment rates and work satisfaction. Conclusions: This feasibility assessment served as the foundation for the future long-term implementation of the Clinical Specialist Radiation Therapist (CSRT) Project. As of 2018, there were 24 CSRTs in Ontario. The APRT role is a natural progression for a readying profession which can play a transformative role in addressing health human resource shortages. Graphical abstract: Image 1 Highlights: An Advanced Practice Radiation Therapist (APRT) is a new role in Ontario, Canada. Definition consisting of seven key traits and a framework, was developed for APRTs. Task-shifting results in program efficiencies and new services. APRT's can have a positive impact on the experiences of their stakeholders.